Constructing religious martyrdom: a cross-cultural study - Soboslai, John (Cambridge University Press, 2024)
"This diverse study offers insights into practices of martyrdom within specific socio-political contexts. Analyzing martyrdom through political theology, John Soboslai examines self-sacrifice in four religious traditions during social and political crises, from second century Christianity in Asia Minor to 21st century Tibetan Buddhism"--